1999
DOI: 10.1097/00012272-199903000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Connecting and Becoming Culturally Competent

Abstract: Addressing how nurses become culturally competent is essential for knowledge development beyond why sociocultural understandings are important. This article reports participatory research conducted during intercultural immersion learning experiences of non-native nurses on an Indian reservation. Emphasizing collaborative relationships within unfamiliar social, political, and economic circumstances, and using Diekelmann's "concernful practices" as an organizing scheme, prompted participants to explicate practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…The empirical literature has identified that cultural competence could be enhanced through educational interventions using workshops (Smith, 1998;Williams, 2002), courses on cultural competence (Crandall, George, Marion, & Davis, 2003;Diaz-Lazaro & Cohen, 2001;Gompertz, 1997;Napholz, 1999), and immersion in a different culture (Fahrenwald, Boysen, Fischer, & Maurer, 2001;Kavanagh, Absalom, Beil, & Schliessmann, 1999;MacAvoy & Lippman, 2001;St. Clair & McKenry, 1999;Walsh & DeJoseph, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The empirical literature has identified that cultural competence could be enhanced through educational interventions using workshops (Smith, 1998;Williams, 2002), courses on cultural competence (Crandall, George, Marion, & Davis, 2003;Diaz-Lazaro & Cohen, 2001;Gompertz, 1997;Napholz, 1999), and immersion in a different culture (Fahrenwald, Boysen, Fischer, & Maurer, 2001;Kavanagh, Absalom, Beil, & Schliessmann, 1999;MacAvoy & Lippman, 2001;St. Clair & McKenry, 1999;Walsh & DeJoseph, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As such, CBPR has been employed in many recent AIAN prevention studies. [59][60][61][62][63][64][65][66][67][68] …”
Section: Cbpr In American Indian and Alaska Native Communitiesmentioning
confidence: 99%
“…Pure ALOHA is featured with the feedback property that enables it to listen to the channel and finds out whether the frame was destroyed. Feedback is immediate in LANs but there is a delay of 270 msec in the satellite transmission [2]. It requires acknowledgment if listening to the channel is not possible due to some reason.…”
Section: Alohamentioning
confidence: 99%